The Success of Climate Change Performance Index in the Development of Environmental Investments: E-7 Countries - Ozarslan Dogan, Basak (Ekonomika, 2025)
Climate change is considered to be one of the biggest problems acknowledged globally today. Therefore, the causes of climate change and solutions to this problem are frequently investigated. For this reason, the purpose of this study is to empirically examine whether the ‘Climate Change Performance Index’ (CCPI) is successful in increasing environmental investments for E-7 countries with the data for the period of 2008–2023. To achieve this aim, the Parks-Kmenta estimator was used as the econometric method in the study. The study findings provide strong evidence that increases in the climate change performance support environmental investments. High climate change performance directs governments and investors toward investing in this area; therefore, environmental investments tend to increase. The study also examined the effects of population growth, real GDP and inflation on environmental investments. Accordingly, it has been concluded that population growth and inflation negatively affect environmental investments, while GDP positively affects environmental investments.